2022
DOI: 10.3390/ani12131686
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Women on Dairy Goat Farms in Southern Spain

Abstract: One of the factors involved in goat milk production is the role of women as farmers. The aim of this study was to evaluate the role of women on dairy goat farms, considering: (1) the profile of women occupationally involved, (2) the organization of the women’s work, (3) the degree of involvement by women in the decision-making on these farms, and (4) the influence of women’s work on productive results. This study was conducted on 52 dairy goat farms in southern Spain. A descriptive analysis and means compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…In recent studies, it was reported that increased workforce on sheep farms has been associated with correct execution of a variety of tasks and positive production outcomes in these flocks [3] and that most predictors associated with the use of antibiotics in sheep farms were related to human resources rather than health management factors [3]. Moreover, Arce et al [48] reported that the presence of women among the farming workforce led to decreased mastitis incidence in farms.…”
Section: Identification Of Risk Factors For Subclinical Mastitismentioning
confidence: 99%
“…In recent studies, it was reported that increased workforce on sheep farms has been associated with correct execution of a variety of tasks and positive production outcomes in these flocks [3] and that most predictors associated with the use of antibiotics in sheep farms were related to human resources rather than health management factors [3]. Moreover, Arce et al [48] reported that the presence of women among the farming workforce led to decreased mastitis incidence in farms.…”
Section: Identification Of Risk Factors For Subclinical Mastitismentioning
confidence: 99%
“…Waithanji et al [14] as cited by Boogaard et al [29] reported that women may be less mobile and more occupied with household tasks, giving them fewer opportunities to sell goats. Caring for young ruminants comes naturally for women [8], and dedicated their work to milking and caring for the kids [15,16]. On the other hand, (male) family members might be helping FHHs to sell an animal, e.g., by transporting it to a sales location.…”
Section: Purpose Of Goat Raisingmentioning
confidence: 99%
“…The systems range from those where goats remain indoors throughout the year, although they have access to outdoor exercise yards [ 11 , 12 ], to those in which the goats graze all year long and most of the day [ 5 , 13 ]. The farms are generally managed by a family labor force and provide economic sustenance to families who live mostly in disadvantaged areas with very few economic and production alternatives [ 14 ].…”
Section: Introductionmentioning
confidence: 99%